Health-related quality of life in haemodialysis patients suffering from chronic itch: results from GEHIS (German Epidemiology Haemodialysis Itch Study) - Weiss, Melanie; Mettang, Thomas; Tschulena, Ulrich; Weisshaar, Elke (Quality of life research, 2016)
Purpose Chronic itch (CI) is a common symptom in haemodialysis (HD) patients affecting about every 4th HD patient. Though it is known that health-related quality of life (HRQOL) is impaired in HD patients, data are lacking on how CI influences HRQOL in this group of patients, also regarding sex differences and the role of sleep and pain. Methods In order to investigate the itch prevalence and to investigate associated factors, GEHIS (German Epidemiology Haemodialysis Itch Study) was established as first cross-sectional study being representative for all dialysis units in Germany by considering their regional distribution and size of the located city according to population. HRQOL of 860 HD patients from a randomly selected cluster sample of 25 dialysis units was investigated using patient-reported outcomes as the Short-Form Health Survey (SF-12), the Hospital Anxiety and Depression Scale (HADS) as well as sleep and pain. Additionally, itch-specific QOL was assessed in HD patients affected by CI using the validated ItchyQoL. Results 42.8 % of HD patients were female. The mean age was 67.2 years (SD ± 13.5). Female patients showed significantly worse values in the mental component summary of the SF-12 as well as in the HADS subscale anxiety compared to male patients. Itch-specific HRQOL did not subject to sex. Patients with impairments in quality of sleep showed significantly worse values in both the SF-12 and the HADS subscales, however not in the ItchyQoL. The occurrence of pain was significantly associated with impaired SF-12, HADS and the ItchyQoL. Multivariate linear regression showed the itch-specific HRQOL to be significantly impaired with rising severity of CI. Conclusions Impairments in HRQOL are a serious problem in HD patients. CI means an additional burden in affected patients, also impairing their HRQOL. GEHIS showed significant sex differences in HRQOL outcomes also in HD patients. CI and pain as well as sleep frequently occur combined and significantly impair HRQOL in HD patients. The care of HD patients should be complemented by psychosocial support and mental health services.